Assentamentos e Ecovila: no caminho da agroecologia - Lozano, Mirian Cristina (2009)
The purpose of this research is to study two experiences of permaculture communities and other sorts of alternative agriculture which are generally considered agroecological practices. I choose two socially distinct experiences for the reason that one of them refers to landless rural workers, whereas the ecovillage is part of an alternative communities middle-class movement. This enables us to identify the social aspects to which it is possible to assign the amount of success of those examples. The communities that have been studied were described following their history, economic and social condition, intellectual and ideological universe; in a way they could be compared to evaluate the process of how to achieve sustainability. I believe that the relevance of studying such experiences is due to the fact that they might constitute the technical support to social projects seeking to empower and to further human development of small and low-resources communities. Especially in the Brazilian context, they can work as frameworks for agrarian reform settlements, traditional communities and family agriculture in general. Ultimately, there is little scientific literature dealing with permaculture and other sorts of alternative agriculture in communities in Brazil. To summarize, there are still several challenges for those communities to achieve self-sufficiency, difficulties which can be overcome and some successes that can be reproduced. Anyhow they are on the road to agroecology